Latino young men and boys in search of justice : testimonies - Acosta, Frank de Jesús; Ramos, Henry A. J., 1959- (Hispanic civil rights series., 2016)
This collection contains first-person testimonials--essays, poetry and letters--by Latino men and boys who have been or are incarcerated, along with articles by system reform advocates. The editors seek to humanize disadvantaged Latino young men while calling attention to the need for a restorative rather than punitive justice system.